Conjugate training for legs muscles in micro cycle of training for competitions among athletes of high qualification in taekwondo WTF - Epov, O. G. (The Russian Journal of Physical Education and Sport, 2018)
The article presents micro cycle with two conjugate trainings for legs muscles, used at special-preparatory stage of sports training among athletes of student sports national taekwondo WTF team of Russia for international competitions during the following period: 2011-2017. Materials. The training micro cycle presents loads distribution and loads parameters according to week days and the time of a day, the methodology of conjugate training for legs muscles is presented. Research methods: scientific-methodical literature analysis and summarizing, methodology, score-sheets analysis. Results. The micro cycle with two conjugate trainings for legs muscles introduction into the training process of student sports national taekwondo WTF team of Russia helped to improve physical and technical-tactical readiness of taekwondo practitioners and win medal places at international competitions. Conclusion. It is recommended to alternate micro cycle with conjugate trainings for legs muscles and the micro cycle, which includes conjugate trainings for hands and shoulder girdle muscles. A complex use of both kinds of micro cycles in the training process of taekwondo practitioners and combatants in general, can provide an optimal sports fitness achievement before the main competitions.